COMPETENCES FOR MANAGING MEGA INFRASTRUCTURE PROJECTS: A PILOT STUDY - Maxwell NYARIRANGWE; Oluwayomi K BABATUNDE (Journal of Construction Project Management and Innovation)
Mega infrastructure projects have been conceptualised as complex adaptive systems characterised by emergence, co-evolution, and self-organisation. These projects have been found to consistently underperform technically, financially, socially, and environmentally, due to gaps in traditional project management practices regarding complexity management. Consequently, project management teams have been compelled to utilise unique processes and complexity management competences. This article is a pilot study of an ongoing PhD research programme. It aims to assess the appropriateness and feasibility of the proposed data-collection methods, sampling frame and data-analysis techniques. It also aims to establish potential logistical challenges and, consequently, to review the methods and processes of the main survey. Semi-structured interviews were used to collect data from five subject experts working on a bus rapid transit project in Polokwane. The results were analysed using content analysis. The findings of the study assisted in highlighting some of the potential logistical challenges which could have been encountered during the main research interviews. The results were also used to assess the appropriateness of the proposed research approach, the sampling frame and size, and the data-collection tool. Overall, the lessons drawn from the findings of the study will be used to review the proposed methods and processes prior to commencement of the main research. Despite the important insights drawn from this study, the data collected will not be used in the main study, but will only be used to improve the associated methods and processes.